Corrosion behavior of titanium alloys in acidic and saline media: role of alloy design, passivation integrity, and electrolyte modification - Bodunrin, Michael O.; Chown, Lesley H.; van der Merwe, Josias W.; Alaneme, Kenneth K.; Oganbule, Christian; Klenam, Desmond E.P.; Mphasha, Nthape P. (Corrosion reviews, 2020)
This paper presents an overview of the corrosion behavior of titanium (Ti) alloys in both acidic and saline solutions. The solutions covered in this review are essentially the typical electrolytes encountered by Ti alloys when applied under service conditions. Although Ti alloys are generally known to be corrosion resistant, this review identifies strong reducing acids and fluoride-containing solutions as electrolytes that corrode Ti and its alloys. The pathways that the knowledge of the corrosion behavior of Ti alloys have followed from the 1950s to date are captured in this review. Based on this, the different factors influencing the corrosion behavior of Ti alloys are highlighted and the different research concepts for improving the corrosion resistance of Ti alloys in both solutions are discussed. The limitations of these research concepts are mentioned and the directions for future research are proposed.